Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar Di Kelas Melalui Penerapan Reward And Punishment Di SDI Wolowona 1 Kabupaten Ende - Elias Rhando (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
Improving the quality of learning in schools is very dependent on several factors. Very important factors include the application of school culture towards improving quality. School culture is a positive thing that must be maintained and implemented by all school residents without feeling compelled. One of the culture of schools that must be maintained is the problem of discipline, including the discipline of the teachers in attending class in the teaching and learning process. In this School Action Research (PTS), an attempt was made in the form of implementing Reward and Punishment for teachers at SDI Wolowona 1, Ende Regency. This research was conducted in two cycles, because from the results of research and data analysis, it turns out that in the second cycle, teacher discipline in class attendance at the teaching and learning process increased and met the indicators set by 75%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance at teaching and learning activities can be done by applying Reward and Punishment to teachers.